On the Move: Incorporating movement, visuals, and compositional techniques derived from the marching arts into non-marching contemporary solos and ensembles - Vincent, Lindsey Louise (Trinity College Dublin. School of Creative Arts. Discipline of Music, 2021)
Marching band has a rich history. It was the original mode of communication and transportation for the military, has shown respect or support for a political stance, and has provided entertainment value. Since the 1970s, the marching arts have flourished in participation, instrumentation, and creative expression. The largest aspect that differentiates this activity from other musical endeavours is movement of the performers. It provides the listener with a visual to accompany the music, providing an extra-sensory experience. The existence of solos, duets, mixed chamber, choir, strings, and orchestra is minimal in the marching community. It is unclear why these performance groups (or soloists) have not been previously composed with movement in mind. However, one culprit for lack of repertoire for choirs and strings could be the absence of a regimented etiquette; although voice would be rather straightforward concerning marching, there are many things to consider when asking a string instrument to march, such as upper body movement and transportation of the cello and double bass. The use of contemporary-style composition and extended techniques is also very limited in this type of performance atmosphere. The six compositions in this portfolio were carefully constructed to acknowledge the physical limitations of instruments and performers while considering the properties of sound on which marching shows are based to provide a unique marching experience. These works are also a reflection of the direction in which the marching arts community can travel, such as the inclusion of soloists and ensembles and with contemporary compositional approaches.
APPROVED
Keywords: Marching band; Marching; Contemporary composition; Requiem; Pageantry; Strings; Marching strings; Choir; Marching choir; Indoor marching; Marching orchestra; Orchestra